CONTROL OF SEVERE BLEEDING EPISODE IN CASE OF GLANZMANN’S THROMBASTHENIA REFRACTORY TO PLATELET TRANSFUSION THERAPY BY ADMINISTERING RECOMBINANT FACTOR VIIa - Javed, Asim; Ayyub, Muhammad; Abrar, S; Mansoor, M; Khan, Badshah; Hussain, T (Journal of Ayub Medical College Abbottabad, 2009)
lanzmann’s thrombasthenia is an autosomal recessive inherited platelet function defect. Though, quantitatively normal, the aggregation ability of platelets is reduced leading to bleeding episodes requiring transfusion of platelet concentrates. We describe a case of 13-year-old girl who had recurrent episodes of epistaxis since birth and was managed with multiple platelet concentrate transfusions and recently admitted with severe epistaxis refractory to platelet transfusion. At this stage administration of recombinant activated factor VII (fVIIa) was considered, which was initially given at 90 µg/kg dose with little control of bleeding but subsequent second dose of 120 µg/kg was administered with excellent response and immediate control of bleeding. Keywords: Glanzmann’s thrombasthenia, autosomal recessive, platelet disorder, recombinant factor VIIa, epistaxis